THE INFLUENCE OF THE SOUTHEAST ASIAN REGIONAL STOCK EXCHANGE ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2017-2018 - Redy Herinanto Albertus (SMBJ: Strategic Management Business Journal, 2021)
This study aims to determine the effect of the South East Asia’s major stock exchanges on the Indonesia Stock Exchange from 2017 to 2018. The main stock exchanges used as independent variables are ^KLCI (Malaysia), ^STI (Singapore), ^SET (Thailand), and ^PSEI (Phillipines). The dependent variable used is ^JKSE (Jakarta Stock Exchange, Indonesia). There are 478 data sets that can be processed, which have been synchronized. By using multiple regression analysis, the results obtained: ^KLCI has a negative and insignificant effect on ^JKSE, ^STI has a negative and insignificant effect on ^JKSE, ^SET has a positive and significant effect on ^JKSE, and ^KLCI, ^STI, ^SET, ^PSEI simultaneously has a significant effect on ^JKSE in the period 2017 to 2018.